Analysis and simulation of welded plates subjected to blast loading - Bonorchis, Dean (Department of Mechanical Engineering, 2024)
At present bIast protection as well as other forms of anti-terrorism measures are a high priority for defence forces and humanit.ar:ia:n organisations. Armoured vehicle used in mine protection and navy ship hulls utilise welding during their fabrication. A weld is defined by British Standards [1], as: “…a union between pieces of metal at faces rendered plastic or liquid by heat or by pressure or by both."